A comparative analysis of sukuk and conventional bonds - (:unkn) unknown (Springer, 2016)
Sukuk and bonds are two kinds of financial instruments; despite their differences, they share similar responsibility of fund mobilizing from surplus (spending) units to shortage units. Sukuk can resemble conventional bonds by some of its features, but it is technically neither debt nor equity. It is complex to understand the exact nature of Sukuk and differentiating them from bonds. Conventional bonds are structured on the basis of debt whereas sukuk are basically investment certificates consisting of ownership claims in a pool of assets. Thus, claim embodied in sukuk is not simply a claim to cash flow but also an ownership claim. Although there are various fundamental differences between the sukuk and conventional bonds, both instruments try to solve the same common financial problem of raising capital for needed entities. They offer solutions in different ways to the same financial problem. Therefore, in this chapter an attempt is made to raise the awareness and knowledge base of those who have had little or no exposure to the Islamic financial instrument, such as sukuk, its complex nature and functions in today’s global financial market. The chapter has compared sukuk instruments with conventional bonds based on the basic fundamental variables such as risks, return, and correlation variables. It has also shown the risk diversification potential of sukuk in a portfolio. © Springer International Publishing Switzerland 2016.
Keywords: Bond; Diversification; F30; G10; G11; G29; Portolio; Return; Risk; Sukuk